2015
DOI: 10.1111/jsm.12886
|View full text |Cite
|
Sign up to set email alerts
|

Psychosexual Well-Being After Childhood Surgery for Anorectal Malformation or Hirschsprung's Disease

Abstract: Introduction Anorectal malformations (ARMs) and Hirschsprung's disease (HD) are congenital malformations requiring pelvic floor surgery in early childhood, with possible sequelae for psychosexual development. Aims To assess psychosexual well-being in adult ARM and HD patients related to health-related quality of life. Methods Eligible for this cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 28 publications
0
34
1
Order By: Relevance
“…Of the few studies on postoperative sexual problems among HD patients, Moore et al [7] noted that 5% of patients reported sexual dysfunction including infertility and erectile dysfunction in males, especially after Duhamel and Swenson procedures. Van den Hondel et al [12] showed in their recent uncontrolled study that 11% of the men with HD had severe erectile dysfunction but no ejaculation difficulties, and that 53% of the women with HD had sexual dysfunction and 20% sexual distress, which, however, were not associated with the length of the aganglionosis or type of operation. Our study did not identify any defects in physical sexual functioning after EPT compared to matched peers, supporting the safety of EPT with regard to preservation of such functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the few studies on postoperative sexual problems among HD patients, Moore et al [7] noted that 5% of patients reported sexual dysfunction including infertility and erectile dysfunction in males, especially after Duhamel and Swenson procedures. Van den Hondel et al [12] showed in their recent uncontrolled study that 11% of the men with HD had severe erectile dysfunction but no ejaculation difficulties, and that 53% of the women with HD had sexual dysfunction and 20% sexual distress, which, however, were not associated with the length of the aganglionosis or type of operation. Our study did not identify any defects in physical sexual functioning after EPT compared to matched peers, supporting the safety of EPT with regard to preservation of such functions.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic dissection close to the rectal wall is the aim of all surgical approaches to HD. Also EPT carries a potential risk to other structures in the vicinity [12,26], although appropriate pelvic dissection within the wall of the distal rectum in EPT should prevent injury to the genitourinary tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with HD can also experience urinary dysfunction (with enuresis in 25%, more nocturnal than in daytime) [43] and sexual dysfunction (11% of male and 53% of female patients) [44]. Growth, urinary and sexual dysfunction were not assessed in this study because of our focus on bowel function.…”
Section: Discussionmentioning
confidence: 99%
“…Schmidt et al 21 found that 65% of the females with anorectal malformations had active sexual life. In the report of van den Hondel et al, 22 87% of females with anorectal malformation were sexually active. In both these studies, the patients were older (all older than 18 years) than in reports concerning cloaca patients; this may influence the rate of sexual activity.…”
Section: Continent (%)mentioning
confidence: 92%